2010
DOI: 10.1590/s1808-18512010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia das fraturas toracolombares cirúrgicas na zona leste de São Paulo

Abstract: OBJETIVO: fazer uma análise prospectiva de cem pacientes com fratura da coluna toracolombar submetidos a tratamento cirúrgico em um hospital terciário da zona leste de São Paulo. MÉTODOS: estudo prospectivo com início em Janeiro de 2006 até Julho de 2009, sendo incluído um total de 100 pacientes com fratura da coluna toracolombar submetidos a tratamento cirúrgico. Avaliou-se o sexo, a idade, o mecanismo de trauma, o déficit neurológico e o tipo de fratura. RESULTADOS: foi observado que queda de altura foi o pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
20

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 15 publications
3
8
0
20
Order By: Relevance
“…Other works 14,18 found an average age five to six years above the one of this study. In Paraná 19 , the average age was 25 years.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Other works 14,18 found an average age five to six years above the one of this study. In Paraná 19 , the average age was 25 years.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 49%
“…In the Santa Marcelina Hospital, Sao Paulo eastern zone 18 , with 100 patients with thoracolumbar fractures, the overall frequency of falls (78%) was significantly higher than motor vehicle accidents (car and motorcycle summing 20%). This study showed that, of 78 falls, 75 were falls from the roof.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 95%
See 3 more Smart Citations